Soybean peroxidase immobilized on δ-FeOOH as new magnetically recyclable biocatalyst for removal of ferulic acid - Tavares, Tássia Silva; Torres, Juliana Arriel; Silva, Maria Cristina; Nogueira, Francisco Guilherme Esteves; da Silva, Adilson C; Ramalho, Teodorico C (Bioprocess and biosystems engineering, 2018)
A significant enhancement in the catalytic performance due to enzymes immobilization is a great way to enhance the economics of biocatalytic processes. The soybean peroxidase (SP) immobilization under ferroxyte and the ferulic acid removal by the enzyme free and immobilized were investigated. The immobilization via silica-coated ferroxyte nanoparticles was effective, and immobilization yield of 39%. The scanning electron microscopy (SEM) images showed significant changes in the materials morphology. Substantial differences were observed in the particles' Fourier Transform Infrared (FTIR) spectra. The magnetic catalyst revealed a better performance than the free enzyme in the ferulic acid conversion, presenting a good V max/K m ratio when compared with the free enzyme. The reuse evaluated by ten cycles exhibited excellent recycling, remaining constant between the sixth and seventh cycles. The use of magnetic nanocatalyst becomes possible to eliminate the high operational costs, and complicated steps of the conventional enzymatic processes. Thus, a viable industrial route for the use of the enzyme as catalyst is possible.
Keywords: enzymy imobilizované; Peroxidase; Iron oxide; Glycine max; kyseliny kumarové; Catalysis; katalýza; Silicon Dioxide; peroxidasa; čištění vody; Wastewater; Waste Water; Water Purification; rostlinné proteiny; oxid křemičitý; Plant Proteins; Biocatalyst; odpadní voda; Bioremediation; Coumaric Acids; Enzymes, Immobilized